2022
DOI: 10.1017/jns.2022.55
|View full text |Cite
|
Sign up to set email alerts
|

Camel milk consumption patterns and perceptions in the UAE: a cross-sectional study

Abstract: Camel milk has been consumed for centuries due to its medicinal and healing properties. The present study aims to investigate the consumption patterns of camel milk and perceived benefits and risks among adults in the United Arab Emirates. A self-administered online questionnaire was developed in English and Arabic languages and was completed online by 852 adults. Socio-demographic characteristics, camel milk consumption patterns and perceived knowledge of the benefits and risks of camel milk were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Intestinal responses start with diarrhea and a loss of appetite. Camel milk has been shown to have a therapeutic impact on autism because it lacks the two caseins found in cow milk linked to autistic symptoms (Ismail et al 2022). and Yagil (2013) found that camel milk was effective in treating autism in the following situations: After 40 days of consuming camel milk, the autistic symptoms of a 4year-old girl completely vanished; A 30-day course of camel milk therapy cured autism in a boy aged 15; Those aged 21 were found to be calmer and less destructive after drinking camel milk for two weeks in a facility for autistic youngsters.…”
Section: Anti-autism Benefits Of Camel Milkmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal responses start with diarrhea and a loss of appetite. Camel milk has been shown to have a therapeutic impact on autism because it lacks the two caseins found in cow milk linked to autistic symptoms (Ismail et al 2022). and Yagil (2013) found that camel milk was effective in treating autism in the following situations: After 40 days of consuming camel milk, the autistic symptoms of a 4year-old girl completely vanished; A 30-day course of camel milk therapy cured autism in a boy aged 15; Those aged 21 were found to be calmer and less destructive after drinking camel milk for two weeks in a facility for autistic youngsters.…”
Section: Anti-autism Benefits Of Camel Milkmentioning
confidence: 99%
“…Pasteurized camel milk has been demonstrated to keep well in the lab for up to 15 days when refrigerated. Milk (produced by Natural Product Company) and milk powder (from camel milk) are two of the camel-related products sold in the Indian market by Sara International company (Yadav et al 2015;Ismail et al 2022). Several components in camel milk were shown to be more heat resistant than those in cow milk, as shown by research by Wernery (2006).…”
Section: Availability Of Camel Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Camel milk, from Camelus dromedarius , is one of the most commonly utilized CAM therapies for diabetes in the Middle East, including the UAE [ 7 , 8 ], especially with the escalating prevalence of diabetes in this region [ 9 , 10 ]. Research has demonstrated that CM has a significant beneficial impact on human nutrition and health, and can be part of CAM because of its multiple functional qualities relevant to the prevention and treatment of many acute and chronic diseases [ 11 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…17-point hedonic scale (smiling faces) was used with frown face (1) = dislike very much. and smile face (7) = like very much 2.…”
mentioning
confidence: 99%